Assessing the Effects of Fuel Subsidy Removal on Students' Academic Achievement (2025)
The paper assessed the effects of fuel subsidy removal on students' academic achievement at university of Ibadan. The descriptive survey research design was adopted with sample consisted of 150 undergraduate students from three faculties of Arts, Education and the Social Sciences (50 from each faculty). The quaestionnaire entitled “Effects of Fuel Subsidy on Students’ Academic Achievement at University of Ibadan Inventory (EFSSAAI)” was the major instrument used for data gathering. Data collected was analyse through descriptive statistics of frequency counts and percentages as well as multiple regression. The paper found that subsidy removal effect (effects (class attendance, course materials and stress level) significantly influence students' academic achivement (F (3,146) = 33.983; R = .641, R2 = .411, Adjusted R2 = .399, p< 0.05), explaining 41.1% of the variance. In light of these result, government and university management should expand financial aid programmes and provide information about scholarship opportunities to support students financially as well as collaborate with local businesses to create part-time job opportunities on or near the campus, enabling students to earn income to cover their living and educational expenses